2022
DOI: 10.1093/biolre/ioac090
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation of the cystic fibrosis transmembrane conductance regulator in the endocervix

Abstract: The Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) is an apical membrane chloride/bicarbonate ion channel in epithelial cells. Mutations in CFTR cause cystic fibrosis (CF), a disease characterized by thickened mucus secretions and is associated with subfertility and infertility. CFTR function has been well characterized in vitro and in vivo in airway and other epithelia studies. However, little is known about CFTR function in the cervix in health and its contribution to cyclic regulation of fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
2
1
Order By: Relevance
“…However, our sample size was limited by resources and ethical considerations, and with endocervical cells harvested from four NHPs, our small sample size may have contributed to lower sensitivity in detecting significant DEGs. While we have demonstrated hormonal control of CFTR expression in prior studies, 71 our CFTR changes here did not meet statistical significance even though expression changes trended in the same direction. There was a much closer association with E2 and P4 treated cells (Figure 4) than those in hormone-free culture, and as a hypothesis generating study, we analyzed a larger "hit" panel, recognizing that there will also be more false positives.…”
Section: Discussioncontrasting
confidence: 84%
“…However, our sample size was limited by resources and ethical considerations, and with endocervical cells harvested from four NHPs, our small sample size may have contributed to lower sensitivity in detecting significant DEGs. While we have demonstrated hormonal control of CFTR expression in prior studies, 71 our CFTR changes here did not meet statistical significance even though expression changes trended in the same direction. There was a much closer association with E2 and P4 treated cells (Figure 4) than those in hormone-free culture, and as a hypothesis generating study, we analyzed a larger "hit" panel, recognizing that there will also be more false positives.…”
Section: Discussioncontrasting
confidence: 84%
“…Another example of a genetic metabolic disease is cystic fibrosis (CF), which is caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene ( Figure 1 ) [ 60 ]. CFTR is a chloride channel that is involved in regulating ion transport across cell membranes, and mutations in this gene lead to abnormal fluid secretion in the lungs, pancreas, and other organs.…”
Section: Genetic Basismentioning
confidence: 99%
“…CFTR expression is multifactorially regulated, and many mechanisms (including hormonal control) cause tissue-specific regulation induced by this gene. A recent study has found that estrogens can increase the presence of CFTR in the uterine epithelium of the oviductal mucosa ( 4 , 5 ). Elements of the glucocorticoid response have been found in the CFTR promoter, and treatment with glucocorticoid changes the expression and activity of CFTR ( 6 ).…”
Section: Introductionmentioning
confidence: 99%